Comparison of 2-dimensional measurement techniques for predicting knee angle and moment during a drop vertical jump - Mizner, R. L.; Chmielewski, T. L.; Toepke, J. J.; Tofte, K. B. (Clinical Journal of Sport Medicine, 2012)
Objective: To determine the association of 2-dimensional (2D) video-based techniques and 3-dimensional (3D) motion analysis to assess potential knee injury risk factors during jump landing.